Biomassa e produtividade subterrânea no cerrado: relações com solo, topografia e fogo - Loiola, Priscilla de Paula (Universidade Federal de São Carlos, 2014)
Plant biomass and productivity are ecological properties that affect community functioning. The belowground biomass of cerrado is underestimated and, therefore, it is important that we know how it is related to biotic and abiotic variables. In the first chapter, we tested for the relationship between different diversity indices and aboveB and belowground biomass. Species diversity and functional divergence positively affected the aboveground biomass, but not the belowground biomass, both in the cerrado and in the seasonal forest. Resource use complementarity led to a better community functioning, but did not predict all the community biomass production, as it disregarded the belowground component. Inclusion of environmental variables and functional traits, in the second chapter, was important to generate models that predicted the belowground biomass. The models were significant, even tough they showed low explanatory power for the cerrado. Foraging for limiting nutrients, altitude, and functional traits related to disturbance were selected in the models predicting the belowground biomass. In the third chapter, we separated fine and coarse roots in two depths. We used structural equation modeling to test for the effects of environmental variables on the belowground biomass in each root category and each depth. We identified soil fertility causing less fine root biomass and recent fire causing less coarse root in the deep soil layer. Shallow root biomass was not caused by any of the ecological processes we studied. Also, aluminum content led to low soil fertility and recent fire caused higher soil fertility, as we expected. The carbon stock of the cerrado and the seasonal forest is large and should not be neglected when estimating the impacts caused by climate and landBuse changes.
Keywords: Ecologia de comunidades; Arvores - anéis de crescimento; Carbono; Diversidade funcional; Floresta estacional semidecidual; Raízes; Carbon; Functional diversity; Ingrowth core; Root; Tropical seasonal forest; CIENCIAS BIOLOGICAS::ECOLOGIA